GOING GLOBAL - ACTING LOCAL: MARKETING STRATEGY OF SIEMENS IN SERBIA - Stojiljkovic, Aleksandra D; Đurić, Slađana (Journal of process management and new technologies, 2018)
When a company has been operating in the world for 170 years, and for 125 years in one specific country, it more than surely deserves to have its business and marketing strategy considered. There are not so many companies that have achieved this and not so many companies can serve as an example of how a global company can be domestic. This is the case with Siemens in the world and Siemens in Serbia, and there is probably no company which has influenced the industrial and economic development of Serbia in such a powerful way as Siemens. This is a sufficient reason for studying the marketing strategy of Siemens, with the focus of this paper on studying the business and marketing strategy of Siemens in Serbia, in order to identify the marketing strategy that has brought this company to global success and which can be used by other companies in their presentation in the global market.